Hubungan Aktivitas Fisik Dengan Kualitas Tidur Pada Lanjut Usia - Fakihan, Ahmad; , Dwi Rosella Komalasari S.Fis., M.Fis., Dipl.Cidesco (2016)
Background: One of problems of elderly is sleep disorders. It relates to physiological changes. Insufficient quality of sleep can is felt when elderly wake up in the morning with unfresh condition. To get a good quality of sleep, good physical activity can improve the quality sleep. Purpose: The purpose of study is to know relations physical activity with the quality of sleep of elderly. Methode: Research method was using observational with cross sectional approach. The sample were 83 elderly who active in the posyandu from 10 posyandus in Gonilan Village of Sukoharjo. Taking sample was using is purposive sampling. Instrument of physical activity was using general practice physical activity questionnaire (GPPAQ ) and quality of sleep use Pittsburgh sleep quality index questioners. Data analysis the research use chi square test with confident interval 95 %. Result: the results of study showed 45 subjects ( 54,2 %) with active category and 38 subjects (45.8 %) with physical activity inactive category. There were 44 subjects (53.0 % ) had fresh qualities sleep, 39 subjects ( 47.0 % ) unfresh qualities of sleep. The results of chi square test obtained value p = 0,007 ( p < 0.05 and OR = 3,429. The conclusion is there was a relations physical activity with the quality of sleep of elderly in posyandu in gonilan village. Subject with active activity physical have 3,429 times opportunity to had have fresh quality of sleep than subject inactive